Integration of Ethno-Counseling in Preserving Local Wisdom Values in Batak Mandailing Traditional Wedding Ceremonies - Ghoffar, Helmi; Ahman, Ahman; Ilfiandra, Ilfiandra (Bulletin of Counseling and Psychotherapy, 2024)
This research aims to explore the application of ethno-counseling in the context of Mandailing Batak marriages, focusing on integrating Dalihan Natolu cultural values ​​in the counseling process. The research method uses a phenomenological and field research approach involving direct observation, interviews, and documentation with1 prospective bride and groom couples who follow this tradition as respondents. This research design is qualitative-based with triangulation data analysis to ensure the validity of the findings. The research results show that ethno-counseling, which integrates values ​​such as "Sadabuat tu jolo" (every action must be accountable) and "Ulang disuan bulu naso marmata" (don't do work in vain), makes a significant contribution to preparing for marriage, improve communication, and deepen cultural understanding between partners. This abstract includes a comprehensive overview of the findings, emphasizing the importance of implementing cultural values ​​in improving counseling practices and supporting harmony in marital relationships.